Habits of Drinking Herbal Medicine in Postpartum Mothers in the Working Area of PD 'Aisyiyah Bangkalan Regency - Anifah, Fulatul; Taufiqoh, Syuhrotut; Nuzula, Firdausi (Journal La Medihealtico, 2024)
The aim of this study is to find out what factors encourage mothers to take herbal medicines and what are the effects after taking herbal medicin. This research method is qualitative descriptive with a case study approach. The research subjects in this study are postpartum mothers who drink herbal medicine with inclusion criteria who do not experience complications during puerperal and are in the postpartum period. The main informants in this study were 5 people with triangulation informants of 4 people consisting of midwives, cadres, families and shamans. The methods used in this study are interviews, FGDs, and observations. The instruments used are interview guidelines and observation sheets.the data obtained is processed, analyzed and presented textually. The results of the study showed that all informants consumed jau for postpartum mothers. All of them consume instant herbal medicine in powder form. Drinking herbal medicine begins at 7 days after giving birth until 40 days of the postpartum period. The driving factor for postpartum mothers to drink herbal medicine is orders from parents and the surrounding community. The efficacy of postpartum herbal medicine felt by the informant was that the body felt healthy, increased breast milk production, tightened muscles, while the negative impact obtained was constipation. The behavior of consuming herbal medicine for postpartum mothers is seen from a medical point of view as not harmful to the health of the postpartum mother's body.